Association of urinary calcium and phosphorus excretion with renal disease progression in type 2 diabetes. (August 2021) - Duan, Suyan; Sun, Lianqin; Zhu, Huanhuan; Nie, Guangyan; Zhang, Chengning; Huang, Zhimin; Zhang, Bo; Xing, Changying; Yuan, Yanggang
Abstract: Objectives: Diabetes is associated with a high incidence of microvascular disease, including nephropathy. The current study aimed to investigate the association of urinary calcium and phosphorus excretion with chronic kidney disease (CKD) progression in type 2 diabetes mellitus. Methods: A total of 159 T2DM patients with chronic kidney disease (CKD stage G1-G4) were retrospectively included. Patients were categorized into three groups according to the tertiles of 24-h urinary calcium and phosphorus excretion, respectively. Clinical parameters and laboratory findings were compared among the three groups. Cox proportional hazards models were used to estimate the associations of urinary calcium and phosphorus excretion with CKD progression and adjusted for baseline eGFR, urinary protein excretion, mean arterial pressure, and use of RAAS inhibitor. A cubic spline curve was used to explore the association between urinary calcium excretion and CKD progression, as well as urinary phosphorus excretion and CKD progression. Moreover, the subgroup effects of urinary calcium and phosphorus excretion on CKD progression were estimated using Cox regression. CKD progression was defined as double of baseline serum creatinine or occurrence of ESRD. Results: During a median of 18.23 months of follow-up, the composite renal outcomes were noted in 27%. Cumulative renal outcomes were significantly lower in the highest tertile of urinary calcium excretion and phosphorus excretion in Kaplan-Meier analyses. The multivariate Cox proportional hazards regression analyses indicated that both the highest tertile of urinary calcium and phosphorus excretion was associated with a lower risk for CKD progression compared with the lowest tertile. Restricted cubic spline analyses of the association between urinary calcium excretion and CKD progression indicated a linear association. Additionally, there was also a linear association between urinary phosphorus excretion and CKD progression. Subgroup analyses showed that higher urinary phosphorus excretion was particularly associated with a lower risk of CKD progression in non-diabetic kidney disease (NDKD) patients. Conclusion: Higher urinary calcium and phosphorus excretion were associated with decreased risk of CKD progression in T2DM patients.